Terroir and rootstock effects on leaf shape in California Central Valley vineyards - Zoë Migicovsky; Joel F. Swift; Mani Awale; Zachary Helget; Laura L. Klein; Leah Pinkner; Karoline Woodhouse; Peter Cousins; Anne Y. Fennell; Allison J. Miller; Daniel H. Chitwood (Plants, People, Planet)
Societal Impact Statement The innumerable effects of terroir—including climate, soil, microbial environment, biotic interactions, and cultivation practice—collectively alter plant performance and production. A more direct agricultural intervention is grafting, in which genetically distinct shoot and root genotypes are surgically combined to create a chimera that alters shoot performance at a distance. Selection of location and rootstock are intentional decisions in viticulture to positively alter production outcomes. Here, we show that terroir and rootstock alter the shapes of grapevine leaves in commercial vineyards throughout the California Central Valley, documenting the profound effects of these agricultural interventions that alter plant morphology. Summary Embedded in a single leaf shape are the latent signatures of genetic, developmental, and environmental effects. In viticulture, choice of location and rootstock are important decisions that affect the performance and production of the shoot. We hypothesize that these effects influence plant morphology, as reflected in leaf shape. We sample 1879 leaves arising from scion and rootstock combinations from commercial vineyards in the Central Valley of California. Our design tests 20 pairwise contrasts between Cabernet Sauvignon and Chardonnay scions from San Joaquin, Merced, and Madera counties from vines grafted to Teleki 5C, 1103 Paulsen, and Freedom rootstocks. We quantify clear differences between Cabernet Sauvignon and Chardonnay leaves. However, we also detect a separate, statistically independent source of shape variance that affects both Cabernet Sauvignon and Chardonnay leaves similarly. We find that this other shape difference is associated with differences in rootstock and location. The shape difference that arises from rootstock and location affects the basal part of the leaf near the petiole, known as the petiolar sinus, and affects its closure. This shape effect is independent from previously described shape differences that arise from genetic, developmental, or size effects.